Self-assembly of supramolecular triarylamine nanowires in mesoporous silica and biocompatible electrodes thereof. Issue 10 (19th February 2016) - Licsandru, Erol-Dan; Schneider, Susanne; Tingry, Sophie; Ellis, Thomas; Moulin, Emilie; Maaloum, Mounir; Lehn, Jean-Marie; Barboiu, Mihail; Giuseppone, Nicolas
Abstract : A layer of oriented mesoporous silica on the surface of a gold electrode is used to template the confined growth of conducting supramolecular triarylamine nanowires. Abstract : Biocompatible silica-based mesoporous materials, which present high surface areas combined with uniform distribution of nanopores, can be organized in functional nanopatterns for a number of applications. However, silica is by essence an electrically insulating material which precludes applications for electro-chemical devices. The formation of hybrid electroactive silica nanostructures is thus expected to be of great interest for the design of biocompatible conducting materials such as bioelectrodes. Here we show that we can grow supramolecular stacks of triarylamine molecules in the confined space of oriented mesopores of a silica nanolayer covering a gold electrode. This addressable bottom-up construction is triggered from solution simply by light irradiation. The resulting self-assembled nanowires act as highly conducting electronic pathways crossing the silica layer. They allow very efficient charge transfer from the redox species in solution to the gold surface. We demonstrate the potential of these hybrid constitutional materials by implementing them as biocathodes and by measuring laccase activity that reduces dioxygen to produce water.